A new epistemology of evidence-based policy. (1st April 2020) - Sayer, Philip
Abstract : In a remarkably short period, 'evidence-based policy' (EBP), and the associated discourses of 'what works', have risen to prominence as a set of organising principles for public policy decision-making. Critics of EBP frequently point to its implicit positivist assumptions by highlighting the socially constructed nature of evidence. However, the effectiveness of this critique is limited by the imprecise and often pejorative use of the term 'positivism'. This article therefore seeks to offer a more precise account of the underlying assumptions of EBP. To do so, it draws on an epistemological position known as process reliabilism, which analyses the justification of a belief by assessing whether it has been reached by means of an epistemically reliable decision-making process or processes. Through this framework, the article advocates a new approach to EBP which is framed around the principle of avoiding error, rather than that of seeking truth.